Water-mediated reduction of [Cu(dmp)2(CH3CN)]2+: implications of the structure of a classical complex on its activity as an anticancer drug. Issue 13 (24th May 2021) - Levín, Pedro; Ruiz, María C.; Romo, Adolfo I. B.; Nascimento, Otaciro R.; Di Virgilio, Ana L.; Oliver, Allen G.; Ayala, Alejandro P.; Diógenes, Izaura C. N.; León, Ignacio E.; Lemus, Luis
Abstract : [Cu(dmp)2 (CH3 CN)] 2+ can be reduced in acetonitrile containing water due to steric constraints of the ligands. Hydroxyl radicals are produced from water oxidation. We take advantage of this reaction to evaluate the anticancer activity of the complex. Abstract : The interplay between coordination geometry and reactivity in copper complexes has been widely studied for years. For Cu II, it is known that the reduction is favored when the geometry is closer to that of the Cu I state, which is mainly tetrahedral. Conversely, the reduction of Cu II complexes in the absence of exogenous reducers has been barely addressed. Herein, we report on the ability of a classic Cu II complex to be partially reduced in acetonitrile solutions containing water, in the absence of external reducers. The role of the structure on the spontaneous reduction is presented by contrasting the geometric features with a related complex, [Cu(phen)2 (CH3 CN)] 2+, which is inert towards the redox process mediated by water. The participation of water in the reduction of [Cu(dmp)2 (CH3 CN)] 2+ is associated with the production of hydroxyl radicals. This, prompted us to evaluate the use of [Cu(dmp)2 (CH3 CN)] 2+ as an anticancer metallodrug, showing an activity stronger than that of [Cu(phen)2 (CH3 CN)] 2+ on 2D and 3D models of bone, lung, and breast cancer cell lines. Furthermore, both complexes are more active than cisplatin. The main mechanism of action is the intracellular ROS generation, with a higher production of cytotoxic species by [Cu(dmp)2 (CH3 CN)] 2+ . Certainly, the performance of [Cu(dmp)2 (CH3 CN)] 2+ as an anticancer agent and its reactivity in the solution phase are connected through the geometrical constraints imparted by the dmp ligands.